Intrinsic normalizations of a nonholonomic hypersurface with m-dimensional generators in affine space An - Kazimieras Navickis (Lietuvos Matematikos Rinkinys)
In this article intrinsic normalizations of a nonholonomic hypersurface with m-dimensional generators in affine space An is constructed in an invariant form.